THE ROLE OF NON-GOVERNMENTAL ORGANIZATIONS IN ENSURING ROAD SAFETY - Usmanova Makhira Nuralievna; Abdurazakova Dildora Anvarovna (Scholar Express Journals, 2022)
The article describes the activities of public organizations and types of business activities in the field of road safety, as well as the priorities for the organization of these activities
Keywords: Business; Road Accidents; Private Sector; Public Organizations